Pengembangan Pemasaran Konten Kampung Cibunut Berwarna Berbasis Pemasaran Otentik dengan Pendekatan Service Learning - Daniel Hermawan; Fransiska Anita Subari; Roni Tua (Warta Pengabdian Andalas, 2023)
Colored Cibunut Village is located in RW 07, Kebon Pisang Urban Village, Sumur Bandung District, Bandung City. Having an eco-friendly creative village concept, Colored Cibunut Village consists of 5 mural zones with various themes, including environment, peace, slave labour, history, and education. In line with a request from the chairman of the Cibunut Finest Movement Foundation to increase brand awareness and the existence of an educational tourism village, both internally and externally from the people living in the Colored Cibunut Village area, it was managed by a team of Business Administration Study Program lecturers, Parahyangan Catholic University focuses on content marketing. Through the MBKM Village Project, students were provided with training for trainers and assisting partners through content marketing and learning the authentic marketing process that forms the local advantage of Colored Cibunut Village. The service learning approach is applied in 3 stages: exploration, application, and evaluation. Partners and students benefit from the MBKM Village Project. Partners gain increased knowledge and skills in content marketing. Meanwhile, students gain valuable experience interacting and implementing the knowledge gained in class to the community in Colored Cibunut Village. The service learning approach provided space for partners, lecturers, and students to complement learning by implementing research manifested in community service.